Uses of Nano-Materials in Different Fields (Bulletin of Pure and Applied Sciences – Physics, 2020)
In this paper, we have discussed various types’ use of nano materials in different  fields like medicine, chemistry & environment, energy, computers &  communications and others which make easy the style of modern human life.